2012
DOI: 10.1017/s0967199412000032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cryostorage on human sperm chromatin integrity

Abstract: The integrity of sperm chromatin structure has proven to be of great importance for human fertility. In this study, we investigated whether sperm cryopreservation has an effect on nuclear DNA tertiary structure, (i.e. condensation), measured by aniline blue staining, in 103 male patients who required consultation for hypo-fertility. Sperm DNA damage was significantly higher in patients showing oligospermia and severe morphological abnormalities than in native sperm populations. Furthermore we observed that chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…As previously suggested (Hammadeh et al, 1999; Fortunato et al, 2012), we also found that cryopreservation alters the spermatozoa's chromatin condensation. The proportion of spermatozoa with noncondensed chromatin appeared to be negatively correlated with sperm viability.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As previously suggested (Hammadeh et al, 1999; Fortunato et al, 2012), we also found that cryopreservation alters the spermatozoa's chromatin condensation. The proportion of spermatozoa with noncondensed chromatin appeared to be negatively correlated with sperm viability.…”
Section: Discussionsupporting
confidence: 88%
“…Lastly, cryopreservation could alter the quality of the spermatozoon's nucleus (for a review, see Royere et al, 1996; Oehninger et al, 2000; Di Santo et al, 2012). Cryopreservation was found to induce chromatin decondensation (as evaluated by aniline blue staining; Hammadeh et al, 1999; Fortunato et al, 2012), or DNA denaturation (as evaluated by an acridine orange test; Spanò et al, 1999; Gandini et al, 2006; Dejarkom and Kunathikom, 2007), whereas another group failed to see negative effects of cryopreservation on chromatin stability when using 1% sodium dodecyl sulfate + 6 mM EDTA (Huret, 1984). More recently, cryopreservation was shown to increase sperm DNA fragmentation (Donnelly et al, 2001; De Paula et al, 2006; Frainais et al, 2010; Zribi et al, 2010; Gosálvez et al, 2011).…”
mentioning
confidence: 99%
“…The chromatin decondensation state is associated with an incorrect sperm maturation during spermiogenesis, when nuclear compaction is caused by a change in nuclear tertiary structure of chromatin due to the substitution of histones with protamines [13,14]. However, recently, our group has also shown a significant impact of cryopreservation on the condensation state of human spermatozoa [15,16] using the nuclear chromatin decondensation test.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm DNA damage is significantly high in patients showing oligospermia (low sperm count) and severe morphological abnormalities [Fortunato et al 2012;Moskovtsev et al 2009]. Correlations were noted between DNA normality and sperm concentration, motility, rapid motility, normal morphology, and head defects [Varghese et al 2009].…”
Section: Implications Of the Main Function Of Sex -Cautions To Considmentioning
confidence: 94%
“…The increase of sperm DNA fragmentation after cryopreservation in liquid nitrogen and thawing is well documented [Riel et al 2011;Thomson et al 2009;Zribi et al 2010]. A recent study of sperm cryostorage techniques found that chromatin decondensation was related to both the type of technique used and the duration of storage [Fortunato et al 2012]. In another study, when compared to fresh samples, cryopreservation in liquid nitrogen and thawing resulted in statistically significant decreases in viability, DNA integrity, and the proportion of motile spermatozoa [Gianaroli et al 2012].…”
Section: Implications Of the Main Function Of Sex -Cautions To Considmentioning
confidence: 96%